2015
DOI: 10.1007/s00404-015-3851-6
|View full text |Cite
|
Sign up to set email alerts
|

LOX-1 gene variants and maternal levels of plasma oxidized LDL and malondialdehyde in patients with gestational diabetes mellitus

Abstract: According to our results, ox-LDL and MDA levels were increased in GDM pregnant women and healthy pregnant women either with or without combined TT/NN genotype carriers, for our Turkish sample, these genotype carriers appear to be related with increased oxidative stress in patients with GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
(37 reference statements)
0
6
0
1
Order By: Relevance
“…The aims of this communication are to provide some evidence to support our claim and to point out a number of technical problems associated with the production, consumption, and analysis of MDA in biological samples. In most of the clinical investigations published in medical journals, including recent works (1-4), simple spectrophotometric analysis (1) or liquid chromatographic analysis (2) of a thiobarbitoric acid (TBA) adduct of MDA as a biomarker of oxidative stress was carried out (19). Despite the wide applications of spectroscopic or chromatographic methods, there were insufficient validation data in the literature.…”
mentioning
confidence: 99%
“…The aims of this communication are to provide some evidence to support our claim and to point out a number of technical problems associated with the production, consumption, and analysis of MDA in biological samples. In most of the clinical investigations published in medical journals, including recent works (1-4), simple spectrophotometric analysis (1) or liquid chromatographic analysis (2) of a thiobarbitoric acid (TBA) adduct of MDA as a biomarker of oxidative stress was carried out (19). Despite the wide applications of spectroscopic or chromatographic methods, there were insufficient validation data in the literature.…”
mentioning
confidence: 99%
“…In addition, increases in the plasma CXCL16 level were closely associated with an increased level of low‐density lipoprotein cholesterol (LDL‐C). LDL‐C is closely associated with oxLDL, and current studies have also confirmed that the level of oxLDL increases in patients with GDM . Sánchez‐Vera et al observed an increased LDL susceptibility to oxidation, whereas Bonet et al demonstrated that oxLDL is cytotoxic to placental cells.…”
Section: The Role Of Cxcl16 In Pathological Pregnancymentioning
confidence: 52%
“…LDL-C is closely associated with oxLDL, and current studies have also confirmed that the level of oxLDL increases in patients with GDM. [109][110][111][112] Sánchez-Vera et al 113 that CXCL16 is essential for the podocyte uptake of oxLDL as a scavenger receptor. Furthermore, they also observed that oxLDL could induce an increase in the expression of CXCL16 in renal podocytes.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…Elevated maternal plasma levels at 28 WOG [292] Oxidized DNA DNA is vulnerable to oxidation and undergoes a continuous cycle of damage and repair in living cells.…”
Section: Description Gdm Status Referencementioning
confidence: 99%